Implementation of International Standard Multicultural Education Through Nature School in Yogyakarta City - Tussholehah, Hilya; Ersa Novia Rachmadiyanti; Rini Febriyani (International Journal of Geography, Social, and Multicultural Education, 2023)
A quality school is a school in which all components respect each other and appreciate the differences of others, so that teaching and learning activities can run effectively in order to achieve goals. Sekolah Tumbuh Yogyakarta is an educational institution established in 2005 that provides formal education consisting of kindergarten (age 4-5 years), elementary (grade 1-6), junior high (grade 7-9), and high school (grade 10-12). Sekolah Tumbuh was established as the embodiment of an educational institution that is provided open to all students without distinguishing one from the other and to facilitate students who need special assistance so as not to feel isolated. Sekolah Tumbuh comes with the aim of being an inclusive school that provides a place for students to become individuals who feel proud of their potential and respect the differences in society